2020
DOI: 10.18662/po/106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Recruitment on Job Candidates’ Perceptions: Evidence from Bangladeshi Fresh Graduates

Abstract: The study intends to identify the impact social media recruitment (SMR) on job candidates" overall perception (OP) in Bangladesh. For this purpose, the authors have employed two independent variables of SMR: perceived advantage (PA) and perceived ease of use (PEU) and three dependent variables: perceived privacy (PP), perceived fairness (PF) and perceived ethics (PE). 877 graduates have been selected through judgment sampling as participants who have completed graduation recently and are looking for jobs. Simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…Although several research studies were conducted focusing on the use of SNSs for searching candidates and hiring, only a few of those studies paid attention on LinkedIn. There are several theoretical and empirical studies that examined the job candidates' perceptions, behaviors and attitude for usage of LinkedIn and other popular SNSs [5][6][7][8][9][10]. On the other hand, some studies investigated particularly on the role LinkedIn profiles to discover the elements that professionals mostly focus on [11][12][13][14].…”
Section: Original Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Although several research studies were conducted focusing on the use of SNSs for searching candidates and hiring, only a few of those studies paid attention on LinkedIn. There are several theoretical and empirical studies that examined the job candidates' perceptions, behaviors and attitude for usage of LinkedIn and other popular SNSs [5][6][7][8][9][10]. On the other hand, some studies investigated particularly on the role LinkedIn profiles to discover the elements that professionals mostly focus on [11][12][13][14].…”
Section: Original Research Articlementioning
confidence: 99%
“…However, as a rational dispute, recruiters are often fairly and lawfully accused of looking for and accumulating personal information from the SNSs such as Facebook that was primarily formed as an individual and social networking platform, not meant to be a job oriented SNS such as LinkedIn. Since several studies indicated the ethical and legal consequences of cyber-vetting [16,17], recruiters are now consistently using SNSs such as LinkedIn to search and recruit competent job candidates [5][6][7][8]. It is particularly reasonable as LinkedIn was initially launched purposefully to permit the possible job candidates to be acknowledged by the hiring organizations.…”
Section: Contents and Hiring Preferences (Hp)mentioning
confidence: 99%
See 1 more Smart Citation
“…SNSs are online communication and sharing platforms where users can share and comment on posts, photos, messages, videos, and events, and indicate "like/love." These platforms are now increasingly being utilized as common platforms for some HR functions such as recruitment, selection, and, most recently, pre-employment background checks (PBCs) by potential employers [3].…”
Section: Introductionmentioning
confidence: 99%
“…SM as a platform provides some information already available for the employers that are not otherwise obtainable elsewhere such as behavioral pattern, hobbies, interests, friend groups etc [35]. In addition, there is an opportunity for the employers to cross check the information that has been already provided to them.…”
Section: Readymade Informationmentioning
confidence: 99%